Do critically ill elderly patients show a different profile than younger patients in terms of prealbumin response to nutrition? Prealbumin response of critically ill elderly patients - Ozgultekin, Asu; Dokuyucu, Ayfer (Progress in Nutrition, 2019)
Nutritional assessment is essential for the clinical nutrition practice.In critical care, prealbumin is still a useful marker for this purpose.Geriatric patient population is increasing in number in critical care and with accompanying comorbidities, they exert different treatment-response profiles.We analysed prealbumin response of critically ill elderly patients compared to younger patients. Methods: 1311 adult patients were included in the 5 years retrospective analysis in our tertiery medical-surgical ICU.Admission levels of prealbumin, albumin, C-reactive protein, as well as CRP/albumin and CRP/prealbumin ratios were compared between the young (<65 years) and elderly (≥65 years)groups of patients, and the relation with outcome was analysed . For the secondary part of the study, patients whose CRP levels persisting over 15mg/L were excluded and 704 patients whose inflammatory response subsided and who were equally fed were analysed for the prealbumin response in the following weeks. The difference between the admission and the outcome levels (died, discharged or the 28th day) of prealbumin were compared within and between the young and elderly groups and their subgroups(died or survived). Results: Prealbumin and albumin levels were significantly higher in young group compared to old group on admission. There were no difference in the admission prealbumin, albumin, CRP levels and CRP/albumin, CRP/prealbumin ratios in the died or survived subgroups of younger patients .Whereas in the older group, admission prealbumin, albumin levels were lower, CRP, CRP/albumin, CRP/prealbumin ratios were significantly higher in died subgroup in terms of the 28th day, and the hospital outcomes (p<0,05).Outcome levels of prealbumin were higher in both groups (p<0,05) but the younger group showed a more pronounced prealbumin response, although in comparison, the mean levels of increase were not statistically significant (p>0,05).In subgroup analysis, mean values of increase between the admission and outcome levels were higher in the survived subgroups (p<0,05). Conclusion: Under the similar protein intake (0,8-1gr/kg/day), geriatric patients showed a blunted response for prealbumin synthesis compared to younger patients.The failure in this response may be due to the chronic inflammatory state, comorbidities and age related physiological organ dysfunctions which make this nutritional marker even less reliable in this age group.